DISTRIBUTIO OF WITHAOLIDE A COTET I VARIOUS ORGAS OF WITHAIA SOMIFERA (L.) DUAL. - P. M. NAIK,; S. H. MANOHAR,; H. N. MURTHY,; N. PRAVEEN, (International Journal of Pharma and Bio Sciences, 2010)
Withanolide A is an important secondary metabolite in Withania somnifera, which is having a high medicinal value and possesses potent anti-tumor and antioxidant properties. Distribution of withanolide A in various organs of Withania somnifera was investigated by High Performance Liquid Chromatography (HPLC) method. The quantitative distribution of withanolide A was different in various organs tested, the accumulation was 386, 342, 272, 206, 102, 56, 35 and 23 µg g-1 DW in shoot tips, leaves, nodes, whole plant, internodes, roots, flowers and seeds respectively. The content of withanolide A gradually decreased from aerial parts i.e., from young leaves to the root. In root, the root tip accumulated higher concentration when compared to middle and basal portion. This study provides the data base for the regulation and control of withanolide A, moreover it provides the scientific evidence for the rational development and utilization of the Withania somnifera resources.